2021
DOI: 10.1152/ajpheart.00914.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 compensates for endothelial nitric oxide synthase deficiency

Abstract: Endothelial cells (ECs) secrete different paracrine signals that modulate the function of adjacent cells; two examples of these paracrine signals are nitric oxide (NO) and neuregulin-1 (NRG1), a cardioprotective growth factor. Currently, it is undetermined whether one paracrine factor can compensate for the loss of another. Herein, we hypothesized that NRG1 can compensate for endothelial NO synthase (eNOS) deficiency. Methods. We characterized eNOS null and wild type (WT) mice by cardiac ultrasound and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…Consonantly, previous studies also demonstrated the protective effects of NRG-1β in a mouse model of type 1 diabetes mellitus and Ang II–induced cardiorenal dysfunction, respectively. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Consonantly, previous studies also demonstrated the protective effects of NRG-1β in a mouse model of type 1 diabetes mellitus and Ang II–induced cardiorenal dysfunction, respectively. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate variant regulation of insulin- and ACh-mediated vasorelaxant responses. Additionally, neuregulin-1, a cardioprotective growth factor, was also shown to compensate for impaired NO production in the aorta of eNOS knockout mice ( Shakeri et al, 2021 ), again demonstrating that alternative pathways may compensate for endothelial NO dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Согласно данным H. Shakeri и соавт. [60], введение NRG-1 предотвращает гипертрофию, фиброз сердца и почек, вызываемый дефицитом эндотелиальной синтазы оксида азота (eNOS); экспрессия NRG-1 регулируется микроРНК-134.…”
Section: нейрегулин-1 при гипертрофии и фиброзе миокардаunclassified